Hubungan Anemia Ibu Hamil dengan Kejadian Stunting pada Balita di UPTD Puskesmas Kampar - Laila, Rahmatul; Syahda, Syukrianti; Lubis, Duma Sari (Evidence Midwifery Journal, 2022)
Globally, about 1 (one) out of 4 (four) or about 26% of children under 5 years old are stunted. In Riau province the incidence of stunting also decreased to 27%. In the working area of ??the Kampar Health Center there are 2 stunting loci, namely Ranah Singkuang village and Jambu Island. The purpose of this study was to determine the relationship between anemia in pregnant women and the incidence of stunting in children under five at the Kampar Health Center UPTD in 2018. The type of research used was quantitative analytic with a case control approach using secondary data. The population is all toddlers who are stunted. The case sample was taken using a total sampling technique and the control sample using a systematic random sampling technique with a total of 53 case respondents and 53 control respondents. Data analysis of this research is univariate and bivariate using chi square test. The result of this research is anemia variable with P-value = 0.017. Based on the results of the study that anemia in pregnant women has a relationship with the incidence of stunting in children under five. It is hoped that the health workers of the Kampar Health Center will optimize socialization to pregnant women and toddlers in order to prevent anemia and stunting and cooperate with families, Katoma and Katoga in the village.